2010
DOI: 10.1002/da.20645
|View full text |Cite
|
Sign up to set email alerts
|

Health anxiety and fear of fear in panic disorder and agoraphobia vs. social phobia: a prospective longitudinal study

Abstract: These results suggest that health anxiety, as well as history of physical diseases, may be specific vulnerability factors for the onset of PDA relative to social phobia. Whereas fear of bodily sensations was not found to be a risk factor for the onset of panic disorder/agoraphobia, it was a specific marker of existing PDA relative to social phobia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 51 publications
1
16
0
Order By: Relevance
“…The data were derived from the Dresden Prediction Study (DPS), a prospective epidemiological study designed to collect data on the prevalence rates, incidence, course, and risk factors of mental disorders in young women (for details about the study see [47–50]). The focus of the DPS was to investigate women during early adulthood because of the high prevalence rates of anxiety disorders in women [51, 52].…”
Section: Methodsmentioning
confidence: 99%
“…The data were derived from the Dresden Prediction Study (DPS), a prospective epidemiological study designed to collect data on the prevalence rates, incidence, course, and risk factors of mental disorders in young women (for details about the study see [47–50]). The focus of the DPS was to investigate women during early adulthood because of the high prevalence rates of anxiety disorders in women [51, 52].…”
Section: Methodsmentioning
confidence: 99%
“…These other aspects of interoception are particularly interesting in light of the fact that some may be maladaptive while others are adaptive [Mehling, ; Mehling et al, ]. For example, excess worry about bodily sensations is associated with panic disorder [Clark, ; Rudaz et al, ; Salkovskis et al, ; Yoris et al, ] and illness anxiety/hypochondriasis [Abramowitz, ], whereas the ability to control attention to body sensation (e.g., as implemented through mindfulness) can be psychologically beneficial [Farb et al, ; Mehling, ]. A characterization of the neural correlates of IS that takes into account the multidimensional nature of interoception could thus inform our understanding of the relationship between body processing and mental and emotional health.…”
Section: Introductionmentioning
confidence: 99%
“…The primary task of the clinician is not psychiatric diagnosis, but to confirm or diagnose physical errors so early diagnosis is difficult [12].In studies, the health concern seen high in hypochondriasis and anxiety [13]. A high level of HA has been shown in various studies in panic disorders [14]. HAI-SF is used in studies and shown that overall HA is to be higher in medical group than healthy group [15].…”
Section: Discussionmentioning
confidence: 99%